Are Replications Mainstream now? A Comparison of Support for Replications Expressed in the Policies of Social Psychology Journals in 2015 and 2022 - Ann-Kathrin Torka; Jens Mazei; Joachim Hüffmeier (Social Psychological Bulletin, 2023)
A decade ago, replications were typically not conducted and appreciated in social psychology, although replications play a central role in ensuring trust in scientific fields. Without systematic replication efforts, it is not clear whether findings are trustworthy. As journals can function as gatekeepers for publications, they can influence whether researchers conduct (and publish) replications. Yet, the scholarly culture in social psychology might have changed over the last decade because numerous highly visible studies did not replicate past findings. In light of these insights and the resulting learning opportunities for the field, we predicted an increase in the expressed support for replications in the policies of social psychology journals from 2015 (i.e., the year the replication problem became widely known) to 2022. We coded whether and how replications were mentioned in the author guidelines on the websites of social psychology journals (N = 51). As expected, replications were welcomed more often in 2022 (25%) than they were in 2015 (12%), but they were not mentioned on the websites of most journals (71% in 2022 vs. 82% in 2015). An exploratory analysis suggested that journals that expressed support for replications on their websites were also more likely to publish articles about replication. Further, exploratory analyses of the journals’ TOP factors indicated similar rates of support for replications as for other rigor and transparency promoting policies. In sum, our findings suggest that appreciation for replication has increased, but is not yet part of mainstream culture in social psychology.